2021
DOI: 10.3390/ijms22031345
|View full text |Cite
|
Sign up to set email alerts
|

BBS Proteins Affect Ciliogenesis and Are Essential for Hedgehog Signaling, but Not for Formation of iPSC-Derived RPE-65 Expressing RPE-Like Cells

Abstract: Bardet-Biedl syndrome (BBS) is a ciliopathy characterized by retinal dystrophy, renal cysts, obesity and polydactyly. BBS genes have been implicated in ciliogenesis, hedgehog signaling and retinal pigment epithelium maturation. BBS1 and BBS5 are members of the BBSome, implicated in cilia transport of proteins, and BBS10 is a member of the chaperonin-complex, mediating BBSome assembly. In this study, involvement of BBS1, BBS5 and BBS10 in ciliogenesis and hedgehog signaling were investigated in BBS-defective pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…New research in an animal model has demonstrated the expression of this pathway modulated in a fasting-dependent manner in hypothalamic neurons [ 58 ]. Other recent studies on BBS1 , BBS5 and BBS10 knock-out human fibroblast lines have shown a reduction in Hh signaling associated with ciliary SMO (smoothened) accumulation [ 59 ]. These results confirm the association of Gli-dependent Hh signaling with BBS proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New research in an animal model has demonstrated the expression of this pathway modulated in a fasting-dependent manner in hypothalamic neurons [ 58 ]. Other recent studies on BBS1 , BBS5 and BBS10 knock-out human fibroblast lines have shown a reduction in Hh signaling associated with ciliary SMO (smoothened) accumulation [ 59 ]. These results confirm the association of Gli-dependent Hh signaling with BBS proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm the association of Gli-dependent Hh signaling with BBS proteins. On the other hand, the same studies have shown an association of Hedgehog signaling with key clinical manifestations present in ALMS and BBS syndromes, such as photoreceptor degeneration and the hyperphagia of central origin, leading to obesity [ 58 , 59 ]. This observation is consistent with the essential role of the primary cilium in Hedgehog signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in IFT are known to cause abnormal SMO localization ( Eguether et al., 2014 ; Keady et al., 2012 ; Liew et al., 2014 ; Yang et al., 2015 ). Abnormal transport could also be caused by a defect in the BBSome ( Hey et al., 2021 ). Overall, these findings indicate that reduced GLI3R levels in combination with defects in protein transport are likely mechanisms leading to increased SHH signaling and to the subsequent ventralization of INPP5E D477N/D477N organoids.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these cells might respond to native Hh ligand or other agonists, but not SAG. There is prior evidence that hTERT RPE-1 and NIH/3T3 cells relocalize SMO and GPR161 and upregulate pathway target genes in response to Hh stimulation (22,29,30). ARPE-19 cells have been used to determine Hh response to cyclopamine, a down-regulator of the pathway (31).…”
Section: Discussionmentioning
confidence: 99%